Endangered Species Act hearings before the Subcommittee on Fisheries and Wildlife Conservation and the Environment of the Committee on Merchant Marine and Fisheries, House of Representatives, Ninety-ninth Congress, first session, on Endangered Species Act reauthorization -- H.R. 1027, March 14, 1985, Endangered Species Act and native American religious practices, June 11, 1985, Captive raptors -- H.R. 2767, July 10, 1985. - United States. Congress. House. Committee on Merchant Marine and Fisheries. Subcommittee on Fisheries and Wildlife Conservation and the Environment. (Washington : U.S. G.P.O., 1985)
vi, 583 p. :